2023
DOI: 10.6007/ijarbss/v13-i1/15728
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Acceptance of E-wallet among Malaysian University Students

Abstract: During the COVID-19 pandemic, many consumers have resorted to contactless payment via e-wallet. This study aims to look into the acceptance of e-wallet applications among Malaysian university students. It investigates the relationship between lifestyle compatibility, perceived usefulness, perceived ease of use and trust and security in terms of their intention to use an e-wallet as a form of payment. Data was collected from 217 respondents in Malaysia using purposive sampling through an online survey. Modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Several studies have highlighted concerns regarding the adoption of e-wallets among young people, including issues related to malware and software, as well as the potential risk of using mobile devices for transactions (Tan, 2019). Seng et al (2023) found that trust and security are the main drivers of e-wallet adoption among Malaysian university students, as many of them still exhibit apprehension towards mobile payments due to security concerns. Nonetheless, it has been revealed that the other characteristics investigated, namely lifestyle compatibility, perceived utility, and perceived ease of use, had a favourable impact on Malaysian university students' propensity to use e-wallets.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have highlighted concerns regarding the adoption of e-wallets among young people, including issues related to malware and software, as well as the potential risk of using mobile devices for transactions (Tan, 2019). Seng et al (2023) found that trust and security are the main drivers of e-wallet adoption among Malaysian university students, as many of them still exhibit apprehension towards mobile payments due to security concerns. Nonetheless, it has been revealed that the other characteristics investigated, namely lifestyle compatibility, perceived utility, and perceived ease of use, had a favourable impact on Malaysian university students' propensity to use e-wallets.…”
Section: Related Workmentioning
confidence: 99%